2018
DOI: 10.1177/0890334418797312
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Related Concerns as Barriers to Exclusive Breastfeeding at 6 Months

Abstract: Mothers' weight, body image and eating concerns, concern regarding their children's weight, and breastfeeding self-efficacy may constitute critical barriers to exclusive breastfeeding at 6 months. Interventions to improve breastfeeding duration and confidence should target maternal body image and eating concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
1
19
0
3
Order By: Relevance
“…Indeed, few studies in which mothers continued breastfeeding up to six months (as recommended by the WHO and UNICEF) remained for analyses. Second, we excluded 10 studies [21][22][23][24][25][26][27][28][29][30] that provided continuous risk estimates because risk with a one unit increase in BMI is exponential, and thus difficult to interpret by combining the different sources of populations. Indeed, the 10 studies [21][22][23][24][25][26][27][28][29][30] vary across countries, BF types, and the length of the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, few studies in which mothers continued breastfeeding up to six months (as recommended by the WHO and UNICEF) remained for analyses. Second, we excluded 10 studies [21][22][23][24][25][26][27][28][29][30] that provided continuous risk estimates because risk with a one unit increase in BMI is exponential, and thus difficult to interpret by combining the different sources of populations. Indeed, the 10 studies [21][22][23][24][25][26][27][28][29][30] vary across countries, BF types, and the length of the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we excluded 10 studies [21][22][23][24][25][26][27][28][29][30] that provided continuous risk estimates because risk with a one unit increase in BMI is exponential, and thus difficult to interpret by combining the different sources of populations. Indeed, the 10 studies [21][22][23][24][25][26][27][28][29][30] vary across countries, BF types, and the length of the follow-up period. Nine studies [21][22][23][24][25][26][27][28][29] were reported from Western countries and three investigated initiation [23,25,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations